2019
DOI: 10.3390/ijms20236069
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Palmitic Acid to Epidermal Morphogenesis and Lipid Barrier Formation in Human Skin Equivalents

Abstract: The outermost barrier layer of the skin is the stratum corneum (SC), which consists of corneocytes embedded in a lipid matrix. Biosynthesis of barrier lipids occurs de novo in the epidermis or is performed with externally derived lipids. Hence, in vitro developed human skin equivalents (HSEs) are developed with culture medium that is supplemented with free fatty acids (FFAs). Nevertheless, the lipid barrier formation in HSEs remains altered compared to native human skin (NHS). The aim of this study is to decip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…Some studies have reported an altered barrier function in skin equivalents developed in vitro compared with native skin. To counter this, Mieremet et al [36] cultured skin equivalents in the presence of free fatty acids. By supplementing the culture medium of human skin equivalents with palmitic acid (PA), a saturated free fatty acid, the researchers hoped to understand the role of PA on skin morphogenesis and barrier formation.…”
Section: Epithelialization and Barrier Function Of The Skinmentioning
confidence: 99%
“…Some studies have reported an altered barrier function in skin equivalents developed in vitro compared with native skin. To counter this, Mieremet et al [36] cultured skin equivalents in the presence of free fatty acids. By supplementing the culture medium of human skin equivalents with palmitic acid (PA), a saturated free fatty acid, the researchers hoped to understand the role of PA on skin morphogenesis and barrier formation.…”
Section: Epithelialization and Barrier Function Of The Skinmentioning
confidence: 99%
“…Although CC-FTM(20+) had further reduced levels of muCERs, the lateral organization was similar compared to FTM(20−). This implicates that in CC-FTM, other factors besides reduced monounsaturation could contribute to the formation of the orthorhombic lateral packing, such as a possible increased ratio of FFA to CER [28,[34][35][36]. Future studies should aim to optimize the ratio of CER/FFA/cholesterol in FTMs, which could promote the formation of the orthorhombic lateral packing.…”
Section: Discussionmentioning
confidence: 94%
“…However, other FA found in sea buckthorn oil may also contribute to skin health. For example, PA, found in sea buckthorn seeds, is known to be abundant in normal human skin; it contributes to an efficient lipid barrier in in vitro models of skin (Mieremet et al, 2019) and is used by cells as a precursor for longer chain saturated FA. It is being used in skin cosmetic products and considered safe for topic administration.…”
Section: Discussionmentioning
confidence: 99%